Ion composition of produced water from coalbed methane wells in western Guizhou, China, and associated productivity response. (1st April 2020) - Zhou, Binyang; Qin, Yong; Yang, Zhaobiao
Highlights: The influence of fracture fluid on produced water was analyzed. The relationships between the main ions in the produced water were analyzed. The criterion for complete flowback of fracturing fluid was analyzed. The Cl − in coal seam water is partially from organic-bound chlorine complexes. High HCO3 − concentration is an indicator for high CBM well productivity. Abstract: The chemical composition of produced water from coalbed methane (CBM) wells provides abundant information regarding the production dynamics of coal reservoirs. In this study, hydro-chemical analyses were conducted on 70 water samples collected in five batches of 21 CBM wells in China's western Guizhou region. The ion composition of the produced water was used to evaluate the fracturing fluid flowback degrees and to predict the productivity of the CBM wells. The results indicate that the water samples could be sorted into two types: (1) the water samples from the Zhijin Block, which had exhibited the characteristics of the original coal seam water, and (2) the water samples from the Songhe and northern Guizhou Blocks, which had been affected by the fracturing fluid. The Na + /Cl − and alkalinity/Cl − ratios, and the Na + /Cl − and Na + /alkalinity ratios exhibit a positive relationship and an exponentially decaying relationship, respectively. In addition, when the concentrations of Cl − are <20 mEq/L, the residual alkalinity shows little variation with the increasing in the Cl − concentrations, which is discretely distributed between 28 and 57 mEq/L. Meanwhile, the other ionic concentrations also tend to be stable. Therefore, in this study, the Cl − concentration of 20 mEq/L is used as the criterion for complete flowback of fracturing fluid. Moreover, the source of the Cl − in the original coal seam water is related to the organic-bound chlorine complexes within the coal. Furthermore, there is a positive correlation between the HCO3 − concentrations and the daily gas production.